Correlation Studies between Self-Efficacy and Art Creation on Visual Impairment Group: A Meta-Analysis - Nur Fajrie; Imaniar Purbasari; Muhammad Sholikhan (STAI Hubbulwathan Duri, 2023)
This study aimed to analyze the relationship between self-efficacy and art creation and whether there was a publication bias in the meta-analysis of research publications. This study explored Scopus and Science Direct databases on research relevant to the limitations of self-efficacy, art creation, visual impairment, and correlation studies in publications between 2014-2022. The data found 117 articles, but ten articles were relevant to correlational studies. The data were analyzed by using the Effect Size test and then used JASP to answer the hypothesis. The Random Effects model analysis showed there was a significant positive relationship between self-efficacy and art creation for visual impairment (z=1.712; p0.005). The results of the Rank Correlation show Kendall's value of 0.244, which indicates the magnitude of the correlation coefficient between effect size and variance. The p-value of 0.381 is more significant than 0.05, which suggests the publication sample data is not publication biased. The study results regarding the perception of visual impairment on the ability to use technology and creative experience using audio correlate with adaptive preparation in the global era. This contributes to the results of research on the actualization needs of visual impairments.